Rhodomyrtone Accumulates in Bacterial Cell Wall and Cell Membrane and Inhibits the Synthesis of Multiple Cellular Macromolecules in Epidemic Methicillin-Resistant Staphylococcus aureus - Ozioma F. Nwabor; Sukanlaya Leejae; Supayang P. Voravuthikunchai (MDPI AG, 2021)
As the burden of antibacterial resistance worsens and treatment options become narrower, rhodomyrtone-a novel natural antibiotic agent with a new antibacterial mechanism-could replace existing antibiotics for the treatment of infections caused by multi-drug resistant Gram-positive bacteria. In this study, rhodomyrtone was detected within the cell by means of an easy an inexpensive method. The antibacterial effects of rhodomyrtone were investigated on epidemic methicillin-resistant Staphylococcus aureus. Thin-layer chromatography demonstrated the entrapment and accumulation of rhodomyrtone within the bacterial cell wall and cell membrane. The incorporation of radiolabelled precursors revealed that rhodomyrtone inhibited the synthesis of macromolecules including DNA, RNA, proteins, the cell wall, and lipids. Following the treatment with rhodomyrtone at MIC (0.5-1 µg/mL), the synthesis of all macromolecules was significantly inhibited (p ≤ 0.05) after 4 h. Inhibition of macromolecule synthesis was demonstrated after 30 min at a higher concentration of rhodomyrtone (4× MIC), comparable to standard inhibitor compounds. In contrast, rhodomyrtone did not affect lipase activity in staphylococci-both epidemic methicillin-resistant S. aureus and S. aureus ATCC 29213. Interfering with the synthesis of multiple macromolecules is thought to be one of the antibacterial mechanisms of rhodomyrtone.